Fuzzy Control of Laparoscopic Surgical Robot Designed for Use in Minimally Invasive Surgery - Aksungur, Serhat; Yakut, Oğuz (PLUSBASE AKADEMİ ORGANİZASYON VE DANIŞMANLIK, 2018)
: Nowadays, the use of robot technologies has become widespread. Robots that have been confronted in many sectors have also been used in surgical operations in recent years. RCM (Remote Center of Motion) mechanisms take the place of these robots, which have less space-consuming and specially designed for operation. Reduced space requirements and lower maintenance costs are the greatest advantages of these mechanisms. In this study, some of the RCM mechanisms which used in surgical operations are mentioned. A unique and original surgical robot designed for laparoscopic surgical purposes which is not in the literature of robots, has been described. This surgical robot was designed with a 3D CAD program and motion of robot was analyzed. Robot control was performed using fuzzy control method. Dynamic equations of robot which used at fuzzy control were obtained with Lagrangian mechanics. MATLAB software has been used for robot control. Used membership function parameters of fuzzy control were optimized with genetic algorithm method. Obtained fuzzy control graphics with MATLAB were given in the result section.
Keywords: Engineering; Mühendislik